Редукційне концептування оракульних схем - Redko, Igor; Yahanov, Petro; Zylevich, Maksym (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2021)
This work is aimed at developing an intersubjective paradigm and an active role of the subject in reduction conceptualization. For this purpose, the general oracular scheme of conceptualization is concretized by the complementarity of composition and decomposition as explications of synthesis and analysis of entities. Pragmatically conditioned enrichment of this complementarity is carried out with the involvement of compositional programming and nominal models of data, functions, and compositions. The oracular scheme of reduction is considered, the meaning of which is that it, based on existing compositions, naturally implements the paradigm of “divide and conquer” in understanding the active role of the subject in conceptualization, supporting the real complementarity of decomposition and compositional methods of conceptualization. Representative examples of reduction conceptualization are shown, which substantiate the technology of solving programming problems.